2018
DOI: 10.1103/physrevb.98.054416
|View full text |Cite
|
Sign up to set email alerts
|

Spin fluctuations in the light-induced high-spin state of cobalt valence tautomers

Abstract: We present a study of the static magnetic properties and spin dynamics in Cobalt valence tautomers (VT), molecules where a low-spin (LS) to high-spin (HS) crossover driven by an intramolecular electron transfer can be controlled by the temperature, by the external pressure or by light irradiation. In the investigated complex, a LS-Co(III) ion bound to a dinegative organic ligand can be reversibly converted into the HS-Co(II) bound to a mononegative one. By combining magnetization measurements with Nuclear Magn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…The transition from a low spin to a high one caused by the intramolecular transfer of the electron was described in detail when the static magnetic properties and spin dynamics in zerosized valence cobalt tautomers was were studied [24]. It was shown that a spin-crossover can be controlled by temperature, external pressure or light radiation.…”
Section: State-of-the-art or Recent Developments Of The Problem Of Mamentioning
confidence: 99%
“…The transition from a low spin to a high one caused by the intramolecular transfer of the electron was described in detail when the static magnetic properties and spin dynamics in zerosized valence cobalt tautomers was were studied [24]. It was shown that a spin-crossover can be controlled by temperature, external pressure or light radiation.…”
Section: State-of-the-art or Recent Developments Of The Problem Of Mamentioning
confidence: 99%
“…While thermally-and photo-induced valence tautomerism has been explored extensively, less is known about pressure-induced valence tautomerism. [6][7][8][9] A family of complexes susceptible to valence tautomerism are [Co(Me n tpa)(dbdiox)] + (Me n tpa = tris(2pyridylmethyl)amine where n = 0-3, corresponds to successive methylation of the 6-position of the pyridine rings, dbdiox = 3,5-di-tert-butyl-1,2-dioxolene). 5-7,9−14 Previous analysis of valence tautomerism in this family of complexes by NMR and electronic spectroscopies, magnetic susceptibility and X-ray diffraction established that the charge distribution of the complex and its response to an external stimulus depends on the extent of methylation of the tpa ligand.…”
Section: Introductionmentioning
confidence: 99%
“…5-7,9−14 Previous analysis of valence tautomerism in this family of complexes by NMR and electronic spectroscopies, magnetic susceptibility and X-ray diffraction established that the charge distribution of the complex and its response to an external stimulus depends on the extent of methylation of the tpa ligand. 5,7,10 ]. (toluene) (denoted hereafter as Me 3 tpa) species were in the HS-Co II -SQ form under ambient conditions in the solid state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While thermally-and photo-induced valence tautomerism has been explored extensively, less is known about pressure-induced valence tautomerism. [6][7][8][9]…”
mentioning
confidence: 99%